Heated humidified high flow nasal cannula versus nasal continuous positive airway pressure for respiratory support in extremely low birth weight preterm infants after extubation: a single centre randomized controlled trial - Gangu, Dhilli Ravindranath; Koripadu, Seshagiri (International Journal of Contemporary Pediatrics, 2020)
Background: The objective of the study was to assess the indications, frequency of usage, clinical efficacy, and safety of heated humidified high-flow nasal cannula (HHHFNC) and nasal continuous positive airway pressure (NCPAP) in extremely low birth weight preterm infants (ELBWI) after extubation. Methods: Hospital based prospective randomized control study involving ELBWI with respiratory distress admitted in NICU. In this study, all selected preterm infants were placed on one of the non-invasive respiratory supports (HHHFNC or NCPAP), after a period of positive pressure ventilation (post-extubation). Reintubation rate within 72 hours after initial extubation, duration of invasive ventilation, duration of non-invasive respiratory support, duration of supplemental oxygen, and time to reach full feeds were the primary outcome measures. Duration of total enteral feeding, average weight gain rate, duration of hospitalization, and complications including nasal injury, IVH, BPD, NEC, ROP, and PDA, were the secondary outcomes. Results: A sample size of 46 ELBWI were included. HHHFNC effectively reduced the incidence of nasal injury and NEC (p<0.05) along with the decreased duration of supplementary oxygen. Additionally, HHHFNC achieved a significant advance in time to reach full enteral feeding; increased the average weight gain before discharge; reduced the duration of hospitalization (p<0.05). Conclusions: HHHFNC was effective in preventing extubation failure in mechanically ventilated preterm ELBWI compared to NCPAP. HHHFNC shortens the duration of supplemental oxygen and significantly reduces the incidence of nasal injury and necrotizing enterocolitis; moreover, it can also reduce the duration of hospitalization and its cost.